TOPOGRAPHIC MAPPING, TEMPERATURE DISTRIBUTION, AND pH OF HOT SPRINGS IN PADANG GANTING, TANAH DATAR, WEST SUMATRA: A PRELIMINARY STUDY - Arif Algifari; Wahyudi Ardiansyah; Ilham Gilang Ramadhan (Universitas Sebelas Maret (UNS), 2024)
This preliminary study explores the hot springs in Padang Ganting, Tanah Datar, West Sumatra, at coordinates 00°34'8.404